Positive electrode material, positive electrode plate, electrochemical energy storage battery and preparation method
By using embedded positive electrode materials in lithium-ion and sodium-ion batteries, the problems of irreversible capacity loss and side reactions are solved, and the performance and stability of the battery are improved.
Patent Information
- Application Number
- CN202310802486.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-31
AI Technical Summary
During the charging and discharging process, lithium-ion and sodium-ion batteries have irreversible capacity loss due to the formation of solid electrolyte interface masks. The existing lithium-ion and sodium-ion materials have poor stability in the air and are prone to side reactions after releasing active ions, which affects battery performance.
The positive electrode material is composed of positive electrode active material agglomerates and active ion supplementary materials. The active ion supplementary materials are embedded in the gaps of the agglomerates and combined with them, improving moisture resistance and stability, reducing side reactions, and forming particles through spray drying and calcining. The positive electrode material is used to improve contact area and structural stability.
It significantly improves the first discharge efficiency and cycle life of the battery, reduces irreversible capacity loss and side reactions, and enhances the moisture resistance and cycle stability of the positive electrode material.
Smart Images

Figure CN119230773A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the field of electrochemical batteries, and in particular to positive electrode materials, positive electrode sheets, electrochemical energy storage batteries and preparation methods. Background Art
[0002] Electrochemical energy storage batteries achieve the purpose of charging and discharging through the mutual conversion of chemical energy and electrical energy. Lithium-ion batteries and sodium-ion batteries are both common types of electrochemical energy storage batteries. Lithium-ion batteries achieve energy storage based on the cyclic flow of lithium ions between the positive and negative electrodes, and sodium-ion batteries achieve energy storage based on the cyclic flow of sodium ions between the positive and negative electrodes. During the charging and discharging operation of lithium-ion batteries and sodium-ion batteries, a solid electrolyte interphase (SEI) will form at the negative electrode. Due to the formation of the solid electrolyte interphase and the irreversible capacity loss caused by the first charge, lithium ions and sodium ions are over-consumed. It can be seen that in order to improve the irreversible capacity loss of lithium-ion batteries and sodium-ion batteries and improve the first charge and discharge efficiency, lithium and sodium supplementation is usually performed in the battery.
[0003] For lithium-ion batteries, the relevant technology mixes lithium-supplementing materials with lithium-based positive electrode active materials and uses them to prepare positive electrode slurry, and uses the lithium-supplementing materials to compensate for the above-mentioned irreversible capacity loss. For sodium-ion batteries, the relevant technology mixes sodium-supplementing materials with sodium-based positive electrode active materials and uses them to prepare positive electrode slurry, and uses the sodium-supplementing materials to compensate for the above-mentioned irreversible capacity loss.
[0004] However, the currently known lithium-supplementing materials and sodium-supplementing materials have poor stability in the air, making them extremely easy to deteriorate. In addition, the residues formed by the lithium-supplementing materials and sodium-supplementing materials after releasing active ions are easily dissolved in the electrolyte and easily produce side reactions, which is not conducive to improving battery performance.
[0005] Public Content
[0006] In view of this, the present disclosure provides a positive electrode material, a positive electrode sheet, an electrochemical energy storage battery and a preparation method, which can solve the technical problems in the related art.
[0007] Specifically, the following technical solutions are included:
[0008] In one aspect, the present disclosure provides a positive electrode material, the positive electrode material comprising a positive electrode active material agglomerate and an active ion supplement material, wherein the positive electrode active material agglomerate is formed by stacking the positive electrode active material;
[0009] The active ion supplement material is located at least in a plurality of gaps of the positive electrode active material agglomerates, and the active ion supplement material is bonded to the positive electrode active material.
[0010] The positive electrode material provided by the embodiment of the present disclosure makes the active ion supplement material located in multiple gaps of the positive electrode active material agglomerate, and the active ion supplement material is combined with the positive electrode active material, so that the active ion supplement material is stably embedded in the positive electrode active material agglomerate without unexpected shedding. The positive electrode material provided by the embodiment of the present disclosure has at least the following advantages: First, the active ion supplement material is located in multiple gaps of the positive electrode active material agglomerate, which can reduce the contact between the active ion supplement material and the air (such as water, carbon dioxide, oxygen, etc.), improve the moisture resistance of the positive electrode material, and prevent it from deteriorating. Second, this can reduce the contact between the residue formed by the active ion supplement material after releasing the active ions and the electrolyte, thereby reducing side reactions. Third, this can reduce the direct contact between the active ion supplement material and the battery slurry, reduce the residual alkali on its surface and the adverse effects on the binder, etc., and increase the slurry stability. Fourth, the active ion supplement material is embedded in the multiple gaps of the positive electrode active material agglomerate in the form of particles, which is conducive to increasing its contact area with the positive electrode active material, reducing the decomposition potential, and facilitating the release of the required capacity at one time. Fifth, the structural unit of the positive electrode active material agglomerate is the positive electrode active material particles that are stacked and in contact with each other, so that their gaps are dispersed. After the active ion supplement material decomposes and releases active ions, the vacancies left in the positive electrode active material agglomerate are also dispersed, which not only does not affect the structural stability of the positive electrode active material agglomerate, but also helps to slowly release structural stress and improve the cycle stability of the positive electrode material. Sixth, the positive electrode material can be directly used to prepare positive electrode plates, which is conducive to simplifying the battery preparation process.
[0011] In some possible implementations, the average particle size of the positive electrode material is 2um-20um, and the average particle size of the active ion supplement material is 10nm-2000nm.
[0012] The average particle size of the positive electrode material is within the above range, which can provide higher rate performance and compaction density, and effectively avoid electrolyte side reactions. The average particle size of the active ion supplement material is within the above range, which can effectively increase the total contact area between the active ion supplement material and the positive electrode material, which is conducive to reducing the decomposition potential and facilitating the one-time release of the required capacity.
[0013] In some possible implementations, based on 100 parts by weight of the positive electrode material, the weight of the active ion supplement material is 1 part to 10 parts.
[0014] In some possible implementations, the density of the positive electrode material is greater than 90%.
[0015] The higher the density of the positive electrode material, the more it can carry active ion supplement materials, and the better the effect of compensating for the irreversible capacity loss of the positive electrode material.
[0016] In some possible implementation manners, between different particles of the positive electrode active material, and between the positive electrode active material and the active ion supplement material, there is carbon单质 and / or carbon compound, and the carbon单质 and / or carbon compound is used to provide chemical bonding force, which can ensure the structural stability of the positive electrode active material agglomerate, and ensure that the active ion supplement material is stably embedded inside the positive electrode active material agglomerate.
[0017] In some possible implementation manners, the mass ratio of the active ion supplement material located in multiple voids of the positive electrode active material agglomerate to the total mass of the active ion supplement material is greater than or equal to 90%.
[0018] In some possible implementation manners, the positive electrode active material agglomerate is formed by stacking lithium-based positive electrode active material phases, and the active ion supplement material is a lithium supplement material.
[0019] In some possible implementation manners, the lithium-based positive electrode active material is selected from at least one of lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, and lithium-rich layered oxide;
[0020] The lithium supplement material is selected from at least one of Li3N, LiF, Li2O2, Li2O, Li x M y O z where 0 < x ≤ 6, 0 < y ≤ 4, 0 ≤ z ≤ 5, and M is selected from at least one of C, S, Si, Fe, Al, Co, Mn, Zn, Ni, Sb, Te, and Ti.
[0021] In some possible implementation manners, the positive electrode active material agglomerate is formed by stacking sodium-based positive electrode active material phases, and the active ion supplement material is a sodium supplement material.
[0022] In some possible implementation manners, the sodium-based positive electrode active material is selected from at least one of sodium vanadium phosphate, sodium fluoro vanadate phosphate, sodium manganese phosphate, sodium iron phosphate, sodium cobalt oxide, sodium manganese oxide, sodium nickel oxide, sodium vanadate, and sodium nickel iron manganese phosphate;
[0023] The sodium supplement material is selected from at least one of Na3N, NaF, Na2O2, Na2O, Na x M y O z where 0 < x ≤ 6, 0 < y ≤ 4, 0 ≤ z ≤ 5, and M is selected from at least one of C, S, Si, Fe, Al, Co, Mn, Zn, Ni, Sb, Te, and Ti.
[0024] In some possible implementations, the positive electrode material further includes a coating layer, which is coated on the outside of the positive electrode active material agglomerate, and the coating layer is used to enhance the structural stability of the positive electrode material and reduce the surface area to reduce side reactions.
[0025] On the other hand, a positive electrode plate is provided, wherein the positive electrode plate comprises any of the positive electrode materials described above.
[0026] The positive electrode plate provided by the embodiment of the present disclosure has all the advantages of the positive electrode materials mentioned above. Exemplarily, the positive electrode plate includes: a positive electrode material layer and a current collector, the positive electrode material layer is located on at least one surface of the current collector, for example, on two opposite surfaces of the current collector, and the positive electrode material layer is prepared using the positive electrode material mentioned above.
[0027] On the other hand, an electrochemical energy storage battery is provided, wherein the electrochemical energy storage battery comprises a positive electrode plate, and the positive electrode plate is as described above.
[0028] The electrochemical energy storage battery provided by the embodiments of the present disclosure has all the advantages of the above-mentioned positive electrode materials. Based on the use of the above-mentioned positive electrode materials, the lost active ions of the electrochemical energy storage battery are replenished, which can effectively improve its initial discharge efficiency and cycle life, and significantly improve its electrochemical performance.
[0029] In some possible implementations, the electrochemical energy storage battery includes a lithium-ion battery or a sodium-ion battery.
[0030] In another aspect, a method for preparing a positive electrode material is provided, wherein the positive electrode material is as described above;
[0031] The preparation method of the positive electrode material comprises:
[0032] The positive electrode active material, the active ion supplement material, the organic binder and the solvent are uniformly mixed to form a raw material solution;
[0033] Under an inert atmosphere, spray drying the raw material liquid to obtain a granular intermediate;
[0034] The granular intermediate is calcined under an inert atmosphere to obtain the positive electrode material.
[0035] The method for preparing the positive electrode material provided by the embodiment of the present disclosure has at least the following advantages: first, the operation steps are simpler, the controllability is strong, and it is easy to scale up industrial production in batches; second, the active ion supplement material will not produce side reactions during the preparation process, thereby ensuring the performance and quality of the positive electrode material and avoiding post-processing; third, multiple types of active ion supplement materials can be used at the same time, making the active ion supplement material more versatile; fourth, the requirements for the particle size of the active ion supplement material and the active material of the positive electrode material are wider, making the preparation method more fault-tolerant.
[0036] In some possible implementations, the solid content of the raw material liquid is 10%-50%, and the viscosity is 1000 cP-5000 cP.
[0037] In some possible implementations, the spray drying operation parameters satisfy at least one of the following parameters: inlet air temperature is 150°C-200°C, outlet air temperature is 90°C-120°C, peristaltic pump speed is 100ml / h-1000ml / h, and nozzle diameter is 0.5mm-2mm.
[0038] By limiting the parameters of the raw material liquid and spray drying as above, the spray granulation effect can be improved so that the particle size of the granular intermediate is within the desired range.
[0039] In some possible implementations, the operating parameters of the calcination process satisfy at least one of the following parameters: the calcination temperature is 400° C.-700° C., and the calcination time is 6 hours-12 hours.
[0040] The purpose of the calcination treatment is to sinter and carbonize the organic binder to form a carbon layer without damaging the structures of the active ion supplement material and the positive electrode active material, so that both maintain their original structures. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 A schematic diagram of the structure of an exemplary positive electrode material provided in an embodiment of the present disclosure;
[0042] Figure 2 A schematic diagram of the structure of an exemplary electrochemical energy storage battery provided in an embodiment of the present disclosure;
[0043] Figure 3 Surface SEM image of the positive electrode material provided in Example 2;
[0044] Figure 4 A cross-sectional SEM image of the positive electrode material provided in Example 2;
[0045] Figure 5 The EDS spectrum of the cross section of the positive electrode material provided in Example 2;
[0046] Figure 6 This is the EDS distribution diagram of the cobalt element in the positive electrode material provided in Example 2;
[0047] Figure 7 This is the EDS distribution diagram of the iron element in the positive electrode material provided in Example 2.
[0048] The reference numerals represent:
[0049] 001. Agglomerates of positive electrode active materials; 002. Active ion supplementary materials; 003. Positive electrode active materials;
[0050] 100, positive electrode sheet; 200, negative electrode sheet; 300, negative electrode sheet; 400, negative electrode sheet; 500, packaging layer. DETAILED DESCRIPTION
[0051] The following will be combined with the drawings in the embodiments of the present disclosure to clearly and completely describe the technical solutions in the embodiments of the present disclosure. Obviously, the described embodiments are part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present disclosure.
[0052] Exemplary embodiments will be described in detail herein, examples of which are shown in the accompanying drawings. When the following description refers to the drawings, the same numbers in different drawings represent the same or similar elements unless otherwise indicated. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present disclosure. Instead, they are merely examples of devices and methods consistent with some aspects of the present disclosure as detailed in the appended claims.
[0053] In the description of the present disclosure, it should be understood that the terms "inside" and "outside" indicate positions or location relationships based on the attached Figure 1 The orientation or position relationship shown is only for the convenience of describing the present disclosure and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation, and therefore cannot be understood as limiting the present disclosure. Figure 1 The relative relationship of the directions shown in the figure is used as the basis, and these direction nouns are used only to more clearly describe the relationship between structures, not to describe absolute directions.
[0054] Lithium-ion batteries and sodium-ion batteries are both electrochemical energy storage batteries, and they both include positive electrodes, negative electrodes, electrolytes, diaphragms, and corresponding circuit components. Among them, lithium-ion batteries achieve energy storage and release by the intercalation and deintercalation of lithium ions between the positive and negative electrodes, and sodium-ion batteries achieve energy storage and release by the intercalation and deintercalation of sodium ions between the positive and negative electrodes. The electrolyte is a carrier for the transmission of lithium ions or sodium ions between the positive and negative electrodes. The diaphragm is ion-conductive but electronically insulated, which can ensure the migration of lithium ions or sodium ions while separating the positive and negative electrodes to prevent short circuits. The positive and negative electrodes rely on the positive electrode materials and negative electrode materials, respectively, to perform energy storage functions.
[0055] When lithium-ion batteries and sodium-ion batteries are charged and discharged, a solid electrolyte interface film will form at the negative electrode. Due to the formation of the solid electrolyte interface film and the irreversible capacity loss caused by the first charge, lithium ions and sodium ions are over-consumed. At present, lithium supplement materials / sodium supplement materials are usually used to make up for the loss of active lithium / active sodium in the battery.
[0056] For lithium-ion batteries, the relevant technology mixes lithium-supplementing materials with lithium-based positive electrode active materials to form positive electrode materials, and uses the positive electrode materials to prepare positive electrode slurry, and uses the lithium-supplementing materials to compensate for the above-mentioned irreversible capacity loss. For sodium-ion batteries, the relevant technology mixes sodium-supplementing materials with sodium-based positive electrode active materials to form positive electrode materials, and uses the positive electrode materials to prepare positive electrode slurry, and uses the sodium-supplementing materials to compensate for the irreversible capacity loss in the initial cycle.
[0057] However, the currently known lithium-supplementing materials and sodium-supplementing materials have poor stability in the air, making them extremely easy to deteriorate. In addition, the residues formed by the lithium-supplementing materials and sodium-supplementing materials after releasing active ions are easily dissolved in the electrolyte and easily produce side reactions, which is not conducive to improving battery performance.
[0058] In view of the technical problems existing in the related art, on the one hand, the embodiments of the present disclosure provide a positive electrode material, Figure 1 An example of a structure of a positive electrode material is shown in FIG. Figure 1 As shown, the positive electrode material includes positive electrode active material agglomerates 001 and active ion supplement materials 002. The positive electrode active material agglomerates 001 are formed by stacking positive electrode active materials 003. The active ion supplement materials 002 are at least located in the gaps of the positive electrode active material agglomerates 001, and the active ion supplement materials 002 are bonded to the positive electrode active materials 003.
[0059] The positive electrode active material exists in the form of particles, and the positive electrode active material agglomerates are formed by stacking a plurality of positive electrode active material particles, thereby forming a plurality of dispersed voids.
[0060] The positive electrode material provided by the embodiment of the present disclosure makes the active ion supplement material located in multiple gaps of the positive electrode active material agglomerate, and the active ion supplement material is combined with the positive electrode active material, so that the active ion supplement material is stably embedded in the positive electrode active material agglomerate without unexpected shedding. The positive electrode material provided by the embodiment of the present disclosure has at least the following advantages: First, the active ion supplement material is located in multiple gaps of the positive electrode active material agglomerate, which can reduce the contact between the active ion supplement material and the air (such as water, carbon dioxide, oxygen, etc.), improve the moisture resistance of the positive electrode material, and prevent it from deteriorating. Second, this can reduce the contact between the residue formed by the active ion supplement material after releasing the active ions and the electrolyte, thereby reducing side reactions. Third, this can reduce the direct contact between the active ion supplement material and the battery slurry, reduce the residual alkali on its surface and the adverse effects on the binder, etc., and increase the slurry stability. Fourth, the active ion supplement material is embedded in the multiple gaps of the positive electrode active material agglomerate in the form of particles, which is conducive to increasing its contact area with the positive electrode active material, reducing the decomposition potential, and facilitating the release of the required capacity at one time. Fifth, the structural unit of the positive electrode active material agglomerate is the positive electrode active material particles that are stacked and in contact with each other, so that their gaps are dispersed. After the active ion supplement material decomposes and releases active ions, the vacancies left in the positive electrode active material agglomerate are also dispersed, which not only does not affect the structural stability of the positive electrode active material agglomerate, but also helps to slowly release structural stress and improve the cycle stability of the positive electrode material. Sixth, the positive electrode material can be directly used to prepare positive electrode plates, which is conducive to simplifying the battery preparation process.
[0061] The positive electrode material provided in the embodiment of the present disclosure is a composite positive electrode material pre-installed with an active ion supplement material. The positive electrode material is also in a granular form, including spherical particles and quasi-spherical particles.
[0062] Exemplarily, the average particle size of the positive electrode material (which can also be understood as the median particle size D50) is 2um-20um, for example, this includes but is not limited to: 3um, 4um, 5um, 6um, 7um, 8um, 9um, 10um, 11um, 12000nm, 13um, 14um, 15um, 16um, 17m, 18um, 19um, 20um, etc.
[0063] The average particle size of the positive electrode material is within the above range, which can provide higher rate performance and compaction density and effectively avoid electrolyte side reactions.
[0064] Furthermore, the active ion supplement material is also in a granular form, which can be embedded in the positive electrode active material agglomerate in the form of primary particles, or in the form of secondary particles. Exemplarily, the average particle size of the active ion supplement material (which can also be understood as the median particle size D50) is 10nm-2000nm, which includes but is not limited to: 10nm, 50nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 800nm, 850nm , 900nm, 950nm, 1000nm, 1050nm, 1100nm, 1150nm, 1200nm, 1250nm, 1300nm, 1350nm, 1400nm, 1450nm, 1500nm, 1550nm, 1600nm, 1650nm, 1700nm, 1750nm, 1800nm, 1850nm, 1900nm, 1950nm, 2000nm, etc.
[0065] In some examples, the average particle size of the positive electrode material can be at least 10 times the average particle size of the active ion supplement material, for example, the average particle size of the positive electrode material is 100-2000 times, further can be 200-1000 times, further can be 300-1000 times the average particle size of the active ion supplement material.
[0066] By making the average particle size of the active ion supplement material within the above range, its particle size is small enough, so that the active ion supplement material contained in the positive electrode material can fully contact with the positive electrode material, thereby effectively increasing the total contact area between the active ion supplement material and the positive electrode material, which is beneficial to reducing the decomposition potential and facilitating the one-time release of the required capacity.
[0067] For the positive electrode material provided in the embodiment of the present disclosure, the particle size range of the active ion supplement material contained therein can be designed to be relatively wide, and the particle size range of the positive electrode active material can also be designed to be relatively wide, which is conducive to improving the versatility of the positive electrode material.
[0068] For the positive electrode material provided in the embodiment of the present disclosure, the type of active ion supplement material contained therein can be a single one or multiple types, such as two, three, four or more, so that it has multiple active ion supplement materials at the same time, which is also conducive to improving the versatility of the positive electrode material.
[0069] For the mass ratio of active ion supplement material to positive electrode active material, please refer to the following: based on 100 parts by weight of positive electrode material, the weight of active ion supplement material is 1-10 parts, that is, the mass percentage of active ion supplement material in positive electrode material is 1%-10%, which includes but is not limited to 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10% and the like.
[0070] The mass percentage of the active ion supplement material is within the above range, ensuring that sufficient active ions are accommodated in the multiple gaps of the positive electrode active material agglomerates, thereby improving the energy density and cycle life of the positive electrode material.
[0071] The positive electrode material involved in the embodiment of the present disclosure has a binding force between the active ion supplement material and the positive electrode active material, so that the two are stably combined. The binding force includes a chemical binding force provided by a chemical bond, and further, it can also include a physical binding force provided by a physical bond, and the physical bond can be a van der Waals bond.
[0072] Regarding the chemical bonding force provided by chemical bonds, for example, between different particles of the positive electrode active material, and between the positive electrode active material and the active ion supplement material, there are carbon simple substance and / or carbon compound, and the carbon simple substance and / or carbon compound are used to provide chemical bonding force.
[0073] The chemical bond can be a covalent bond formed between the carbon element and other elements in the active ion supplement material and the positive electrode active material, that is, there is a carbon element and / or a carbon compound between the contact interface between the active ion supplement material and the positive electrode active material, and their structural form can be at least one of a layer, a block, and a discrete point. The carbon element and / or the carbon compound between the active ion supplement material and the positive electrode active material can be a continuous structure or a discontinuous structure. The carbon element and / or the carbon compound can not only achieve a stable combination and contact between the active ion supplement material and the positive electrode active material, but also help to enhance the activity of the positive electrode active material, thereby significantly improving the electrochemical performance of the positive electrode material.
[0074] In the embodiment of the present disclosure, the mass percentage of carbon element and / or carbon compound in the positive electrode material is 1%-10%. The mass percentage of carbon element and / or carbon compound within the above range can not only achieve full combination of all active ion supplement materials with the positive electrode active material, but also has the effect of improving the electrochemical performance of the positive electrode material.
[0075] The term "and / or" in the embodiments of the present disclosure is merely a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent three situations: A exists alone, A and B exist at the same time, and B exists alone.
[0076] The positive electrode active material agglomerates are formed by stacking the positive electrode active material phases, so that there are multiple gaps, i.e., vacancies, on the positive electrode active material agglomerates, and the vacancies are occupied by the active ion supplementary material, thereby forming a positive electrode material in the form of a composite material. It is expected that the density of the positive electrode material involved in the embodiment of the present disclosure is greater than 90%, that is, the porosity of the positive electrode material is less than 10%.
[0077] Exemplarily, the density of the positive electrode material is greater than or equal to 95%, further, the density of the positive electrode material is greater than or equal to 96%, further greater than or equal to 97%, further greater than or equal to 98%, further greater than or equal to 99%, further equal to 100%.
[0078] The higher the density of the positive electrode material, the more it can carry active ion supplement materials, and the better the effect of compensating for the irreversible capacity loss of the positive electrode material.
[0079] The embodiments of the present disclosure expect that the active ion supplement materials are all located in the multiple gaps of the positive electrode active material agglomerates, that is, located inside the positive electrode active material agglomerates, which is particularly beneficial for reducing the contact between the active ion supplement materials and the air, electrolyte, slurry, etc. However, considering that during the preparation process, it is not excluded that some active ion supplement materials are bound to the outer surface of the positive electrode active material agglomerates.
[0080] Exemplarily, the mass ratio of the mass of the active ion supplement material located in the multiple gaps of the positive electrode active material agglomerates to the total mass of the active ion supplement material is greater than or equal to 90%, for example, this includes but is not limited to greater than or equal to 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, further, the mass ratio of the mass of the active ion supplement material located in the multiple gaps of the positive electrode active material agglomerates to the total mass of the active ion supplement material can be 100%.
[0081] In some examples (1), the positive electrode material is a lithium-based positive electrode material, which can be used in lithium-ion batteries. Accordingly, the positive electrode active material agglomerates involved in the positive electrode material are formed by stacking of lithium-based positive electrode active materials, and the active ion supplement material is a lithium supplement material.
[0082] Some applicable lithium-based cathode active materials are selected from at least one of lithium iron phosphate, lithium iron manganese phosphate, lithium cobaltate, lithium nickelate, lithium manganate, lithium nickel cobalt manganate, and lithium-rich layered oxides. Among them, the chemical formula of lithium nickel cobalt manganate is LiMO2, where M is a nickel-cobalt-manganese ternary compound, and the atomic percentages of nickel, cobalt, and manganese elements can be in any ratio. For example, the atomic percentage of nickel is 80%, the atomic percentage of cobalt is 10%, and the atomic percentage of manganese is 10%.
[0083] Some applicable lithium supplement materials are selected from at least one of Li3N, LiF, Li2O2, Li2O, Li x M y O z where 0 < x ≤ 6, 0 < y ≤ 4, 0 ≤ z ≤ 5, and M is selected from at least one of C, S, Si, Fe, Al, Co, Mn, Zn, Ni, Sb, Te, and Ti.
[0084] For Li x M y O z where the value of x includes but is not limited to 1, 2, 3, 4, 5, 6, the value of y includes but is not limited to 1, 2, 3, 4, and z includes but is not limited to 0, 1, 2, 3, 4, 5, etc. For example, Li x M y O z can be Li6CoO4, Li5FeO4, Li2C2O4, etc.
[0085] It can be seen that for the lithium-based cathode material provided by the embodiments of the present disclosure, the types of applicable lithium-based cathode active materials and lithium supplement materials are more extensive and have stronger versatility.
[0086] In some examples (2), the cathode material is a sodium-based cathode material, which can be used in sodium-ion batteries. Correspondingly, the cathode active material aggregates involved in the cathode material are formed by stacking sodium-based cathode active material phases, and the active ion supplement material is a sodium supplement material.
[0087] Some applicable sodium-based cathode active materials are selected from at least one of sodium vanadium phosphate, sodium fluoro vanadate phosphate, sodium manganese phosphate, sodium iron phosphate, sodium cobaltate, sodium manganate, sodium nickelate, sodium vanadate, and sodium nickel iron manganate.
[0088] Some applicable sodium supplement materials are selected from at least one of Na3N, NaF, Na2O2, Na2O, Na x M y O z where 0 < x ≤ 6, 0 < y ≤ 4, 0 ≤ z ≤ 5, and M is selected from at least one of C, S, Si, Fe, Al, Co, Mn, Zn, Ni, Sb, Te, and Ti.
[0089] For Na x M y O z , where x includes but is not limited to 1, 2, 3, 4, 5, 6, y includes but is not limited to 1, 2, 3, 4, z includes but is not limited to 0, 1, 2, 3, 4, 5, etc. For example, Na x M y O z It can be Li6CoO4, Na5FeO4, Na2C2O4, etc.
[0090] It can be seen that the sodium-based positive electrode material provided by the embodiment of the present disclosure is applicable to a wider range of types of lithium-based positive electrode active materials and lithium supplement materials, and has stronger versatility.
[0091] In some implementations, the positive electrode material provided by the embodiments of the present disclosure further includes a coating layer, which is coated on the outside of the positive electrode active material agglomerate, and the coating layer is used to enhance the structural stability of the positive electrode material and reduce the surface area to reduce side reactions.
[0092] A coating layer with good mechanical properties can be used to give it better toughness and fatigue resistance, thereby alleviating the volume expansion problem of the positive electrode active material agglomerates and improving its structural stability.
[0093] Exemplarily, the material of the coating layer includes but is not limited to metal fluoride, metal carbide, metal oxide, polymer, etc.
[0094] Exemplarily, the metal elements involved in the above-mentioned metal fluorides, metal carbides, and metal oxides include, but are not limited to: nickel, cobalt, aluminum, manganese, lithium, potassium, barium, iron, calcium, copper, zinc, titanium, magnesium, zirconium, strontium, chromium, tin, antimony, tungsten, niobium, molybdenum, vanadium, palladium, bismuth, cesium, hafnium, tantalum, polonium, gallium, indium, thallium, yttrium, scandium, and at least one of the lanthanide elements.
[0095] The polymers involved above include but are not limited to: at least one of polypyrrole and its modified products, polythiophene and its modified products, polyamide and its modified products, polyethylene oxide and its modified products, polyvinylidene fluoride and its modified products, polyacrylate polymers and its modified products, polyacrylonitrile polymers and its modified products, polyether polymers and its modified products, polysiloxane and its modified products or polyanion single ion conductor type polymers.
[0096] Exemplarily, the thickness of the coating layer ranges from 2 nm to 100 nm, including but not limited to 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, etc.
[0097] On the other hand, an embodiment of the present disclosure further provides a positive electrode plate, which includes any one of the positive electrode materials described above.
[0098] The positive electrode plate provided in the embodiments of the present disclosure has all the advantages of the positive electrode materials mentioned above.
[0099] Exemplarily, the positive electrode plate includes: a positive electrode material layer and a current collector, the positive electrode material layer is located on at least one surface of the current collector, for example, on two opposite surfaces of the current collector, and the positive electrode material layer is prepared using the above-mentioned positive electrode material.
[0100] Based on the positive electrode material provided in the embodiment of the present disclosure, the embodiment of the present disclosure further provides a positive electrode material system, which includes: any one of the positive electrode materials described above, a binder and a conductive agent.
[0101] In some examples, the weight percentage of the positive electrode material in the positive electrode material system is 80wt% to 98wt%; the weight percentage of the binder in the positive electrode material system is 1wt% to 15wt%; and the weight percentage of the conductive agent in the positive electrode material system is 1wt% to 15wt%.
[0102] For example, the weight percentage of the positive electrode material in the positive electrode material system includes but is not limited to: 80wt%, 81wt%, 82wt%, 83wt%, 84wt%, 85wt%, 86wt%, 87wt%, 88wt%, 89wt%, 90wt%, 91wt%, 92wt%, 93wt%, 94wt%, 95wt%, 96wt%, 97wt%, 98wt%, etc. The weight percentage of the binder in the positive electrode material system includes but is not limited to: 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, etc. The weight percentage of the conductive agent in the positive electrode material system includes but is not limited to: 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, etc.
[0103] The binder is used to bond the active material, the conductive agent and the current collector. In some examples, the binder is at least one of polyvinylidene fluoride, carboxymethyl cellulose-based binder, styrene-butadiene rubber-based binder, polyimide-based binder, polyacrylic acid-based binder, polyacrylonitrile-based binder and polyvinyl alcohol-based binder.
[0104] Conductive agents are used to improve the electronic conductivity of the pole piece, and do not provide additional capacity or cause additional chemical reactions. Some applicable conductive agents include, but are not limited to, at least one of conductive graphite, conductive carbon black, acetylene black, carbon nanotubes, and graphene. The use of the above conductive agents can achieve the purpose of reducing the impedance of the positive pole piece and improving the rate performance.
[0105] Exemplarily, the preparation method of the positive electrode sheet is as follows:
[0106] The binder is dissolved in a polar solvent to obtain a glue solution; the glue solution is mixed with a positive electrode material and a conductive agent, and stirred evenly to obtain a positive electrode slurry; the positive electrode slurry is coated on at least one surface of a current collector, and sequentially dried and rolled to obtain a positive electrode sheet.
[0107] In order to improve the quality of the positive electrode sheet, the positive electrode slurry can be degassed and screened, and then coated on the surface of the current collector.
[0108] In some examples, the current collector includes, but is not limited to, at least one of a copper foil, a copper mesh, a carbon-coated copper foil, a stainless steel foil, and a nickel foil.
[0109] In some examples, the polar solvent includes, but is not limited to, at least one of N-methylpyrrolidone, dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide, and cyclohexanone.
[0110] On the other hand, the embodiments of the present disclosure further provide an electrochemical energy storage battery, which includes a positive electrode plate, and the positive electrode plate is as described above.
[0111] The electrochemical energy storage battery provided by the embodiments of the present disclosure has all the advantages of the above-mentioned positive electrode materials. Based on the use of the above-mentioned positive electrode materials, the lost active ions of the electrochemical energy storage battery are replenished, which can effectively improve its initial discharge efficiency and cycle life, and significantly improve its electrochemical performance.
[0112] As attached Figure 2 As shown, the electrochemical energy storage battery includes, in addition to the above-mentioned positive electrode sheet 100, a negative electrode sheet 200, an electrolyte 300, a separator 400, and a packaging layer 500. The electrolyte 300 is filled in the space between the positive electrode sheet 100 and the negative electrode sheet 200, and the separator 400 is located in the electrolyte 300 to isolate the positive electrode sheet 100 from the negative electrode sheet 200. The packaging layer 500 is used to encapsulate the positive electrode sheet 100, the negative electrode sheet 200, the electrolyte 300, and the separator 400 as a whole.
[0113] The electrochemical energy storage battery realizes energy storage and release by the intercalation and deintercalation of active ions between the positive electrode sheet 100 and the negative electrode sheet 200. The electrolyte 300 is a carrier for the transmission of active ions between the positive electrode sheet 100 and the negative electrode sheet 200. The diaphragm 400 is ion conductive but electronically insulating. The diaphragm 400 is used to ensure the migration of active ions while separating the positive electrode sheet 100 and the negative electrode sheet 200 to prevent short circuit.
[0114] In some examples, the electrochemical energy storage battery includes a lithium-ion battery and a sodium-ion battery. As an example, the electrochemical energy storage battery is a lithium-ion battery. As another example, the electrochemical energy storage battery is a sodium-ion battery.
[0115] On the other hand, an embodiment of the present disclosure further provides a method for preparing a positive electrode material, wherein the positive electrode material is as described above.
[0116] The preparation method of the positive electrode material comprises:
[0117] Step S1, uniformly mix the positive electrode active material, the active ion supplement material, the organic binder and the solvent to form a raw material solution.
[0118] Step S2: spray-drying the raw material liquid under an inert atmosphere to obtain a granular intermediate.
[0119] Step S3: calcining the granular intermediate under an inert atmosphere to obtain a positive electrode material.
[0120] Through step S1, a uniformly mixed raw material solution is formed, so that the active ion supplement material is uniformly dispersed between the positive electrode active materials. The organic binder is used to bind the positive electrode active material and the active ion supplement material to form particles, and after calcination, a carbon layer can be formed to bind the active ion supplement material to the positive electrode active material.
[0121] In step S2, the raw material liquid is spray-dried to achieve granulation to form a granular intermediate, wherein at least 90% of the solvent will be volatilized after spray drying.
[0122] The spray drying granulation method has at least the following advantages: First, it integrates the functions of mixing, granulation, and drying, and can make the raw material liquid into granules in one step, shorten the drying time, and improve the efficiency of granulation and drying. Second, it can make the active ion supplement material evenly dispersed in the positive electrode active material agglomerates formed by the close accumulation of positive electrode active materials. Third, the control of the average particle size of the formed positive electrode active material agglomerates and active ion supplement materials is more accurate and convenient.
[0123] In step S3, the granular intermediate is calcined to carbonize the organic binder into a carbon layer, thereby achieving a stable combination between the positive electrode active material and the active ion supplement material. At the same time, the solvent and some impurities are further thoroughly removed to prepare the positive electrode material.
[0124] It can be seen that the preparation method of the positive electrode material provided by the embodiment of the present disclosure has at least the following advantages: first, the operation steps are simpler, the controllability is strong, and it is easy to scale up industrial mass production; second, the active ion supplement material will not produce side reactions during the preparation process, thereby ensuring the performance and quality of the positive electrode material and avoiding post-processing; third, multiple types of active ion supplement materials can be used at the same time, making the general range of active ion supplement materials wider; fourth, the requirements for the particle size of the active ion supplement material and the active material of the positive electrode material are wider, making the preparation method more fault-tolerant.
[0125] The following is a further description of the above steps and their functions:
[0126] For step S1, the amount of the active ion supplement material and the positive electrode active material can be determined according to their mass ratio. The active ion supplement material and the positive electrode active material with a specific ratio are dispersed in a solvent pre-dispersed with an organic binder, and stirred evenly to obtain a raw material liquid with a uniform texture.
[0127] The solid content of the raw material liquid is 10%-50%, including but not limited to 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, etc. The viscosity of the raw material liquid is 1000cP-5000cP, including but not limited to 1000cP-2000cP, 1000cP-3000cP, 2000cP-4000cP, 3000cP-4000cP, 3000cP-5000cP, etc.
[0128] The solid content referred to here refers to the ratio of the total mass of the active ion supplement material and the positive electrode active material to the mass of the raw material solution.
[0129] By limiting the solid content and viscosity of the raw material liquid as mentioned above, the thickening of the raw material liquid is ensured to facilitate rapid granulation in the subsequent spray drying process, and this is also particularly beneficial for controlling the particle size of the formed particles within the desired range, because the embodiment of the present disclosure expects the average particle size of the final positive electrode material to be 2um-20um, and the average particle size of the active ion supplement material to be 10nm-2000nm.
[0130] The solvent plays a dispersing role here, and it is expected that the solvent is easily volatilized at a certain temperature to avoid remaining in the positive electrode material. Some suitable solvents include but are not limited to at least one of N-methylpyrrolidone, ether, dichloromethane, benzene, tetrachloromethane, and chloroform.
[0131] Some suitable organic binders include, but are not limited to, at least one of glucose, polyacrylonitrile, polyvinylidene chloride, polyvinylidene chloride-hexafluoropropylene, polytetrafluoroethylene, polyethylene oxide, polyamide, polyamideimide, polymethyl methacrylate, polycarbonate, carboxymethyl cellulose, styrene-butadiene copolymer, polyacrylonitrile, sodium carboxymethyl cellulose or styrene-butadiene rubber.
[0132] The content of the organic binder may be sufficient to ensure that the solid content and viscosity of the raw material liquid are within the above-specified ranges. For example, the mass percentage of the organic binder in the raw material liquid may be 1%-5%.
[0133] The operating parameters of spray drying can affect the particle size of the granular intermediate, as well as the uniform dispersion effect of the active ion supplement material therein. In the embodiment of the present disclosure, it is expected that the operating parameters of spray drying satisfy at least one of the following parameters so as to obtain excellent spray granulation effect: the inlet air temperature is 150°C-200°C, the outlet air temperature is 90°C-120°C, the peristaltic pump speed is 100ml / h-1000ml / h, and the nozzle diameter is 0.5mm-2mm.
[0134] For example, the air inlet temperature includes but is not limited to: 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C, 200°C, etc. The air outlet temperature includes but is not limited to: 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, etc. The peristaltic pump speed includes but is not limited to: 100ml / h, 200ml / h, 300ml / h, 400ml / h, 500ml / h, 600ml / h, 700ml / h, 800ml / h, 900ml / h, 1000ml / h, etc. The nozzle diameter includes but is not limited to: 0.5mm, 0.6mm, 0.7mm, 0.8mm, 0.9mm, 1mm, 1.1mm, 1.2mm, 1.3mm, 1.4mm, 1.5mm, 1.6mm, 1.7mm, 1.8mm, 1.9mm, 2mm, etc.
[0135] By defining the spray drying operating parameters as above, the active ion supplement material in the granular intermediate is uniformly dispersed in multiple gaps of the positive electrode active material agglomerates, and the average particle size of the granular intermediate is 2um-20um, and the average particle size of the active ion supplement material is 10nm-2000nm.
[0136] In the disclosed embodiment, the purpose of the calcination treatment is to sinter and carbonize the organic binder to form a carbon layer without damaging the structure of the active ion supplement material and the positive electrode active material, so that both maintain their original structure. Based on this, the operating parameters of the calcination treatment meet at least one of the following parameters: the calcination temperature is 400°C-700°C, and the calcination time is 6 hours-12 hours.
[0137] For example, the calcination temperature includes but is not limited to 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, etc.; the calcination time includes but is not limited to 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, etc.
[0138] The spray drying and calcination treatments are both performed under an inert atmosphere. For example, the inert atmosphere may be a nitrogen atmosphere, an argon atmosphere, or the like.
[0139] Furthermore, the method for preparing the positive electrode material provided in the embodiment of the present disclosure may also include screening the particles of the prepared positive electrode material to collect the positive electrode material with a particle size within a desired range.
[0140] The present disclosure will be further described below by more specific examples. Although some specific embodiments are described below, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments set forth herein. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in the art or the product instructions are used, and where the manufacturers of the reagents or instruments are not indicated, they can all be conventional products that can be obtained commercially.
[0141] Example 1
[0142] This embodiment 1 provides a lithium-based positive electrode material, a 1# positive electrode plate prepared based on the lithium-based positive electrode material, and a 1# lithium-ion battery obtained based on the 1# positive electrode plate.
[0143] The lithium-based positive electrode material includes a positive electrode active material agglomerate and an active ion supplement material, wherein the positive electrode active material agglomerate is formed by stacking the positive electrode active material lithium iron phosphate (LiFePO4); the active ion supplement material is Li6CoO4, which is at least located in multiple gaps of the positive electrode active material agglomerate, and the active ion supplement material is combined with the positive electrode active material through the chemical binding force provided by the carbon layer. Among them, the average particle size of the positive electrode material is 2um-20um, 10um-15um, the average particle size of the active ion supplement material is 500nm-1000nm, and the mass ratio of the active ion supplement material located in the multiple gaps of the positive electrode active material agglomerate to the total mass of the active ion supplement material is greater than 95%.
[0144] The preparation method of the positive electrode material is as follows: 10g of polyacrylonitrile is dispersed in 200mL of N-methylpyrrolidone in advance, and then 95g of lithium iron phosphate (LiFePO4, D50 is 0.9um) and 5g of Li6CoO4 (D50 is 1um) are added thereto, and stirred and mixed at room temperature for 20min to form a raw material liquid with a solid content of 10%. Under an argon atmosphere, the raw material liquid is spray-dried to obtain a granular intermediate, wherein the spray drying temperature is 160°C. Under an argon atmosphere, the granular intermediate is calcined to obtain a positive electrode material. Wherein, the calcination temperature is 650°C and the calcination time is 8 hours. After the calcination treatment, the temperature is naturally lowered to obtain the lithium-based positive electrode material of Example 1, which is a LiFePO4@Li6CoO4 composite material.
[0145] The preparation method of the 1# positive electrode plate is as follows: 48g of the above-mentioned lithium-based positive electrode material is mechanically mixed with 0.5g of carbon nanotubes and 1.5g of polyvinylidene fluoride, and then N-methylpyrrolidone is added as a solvent to prepare a slurry with a solid content of 65wt% and stirred evenly to obtain a uniform positive electrode slurry. The positive electrode slurry is coated on an aluminum foil current collector with a thickness of 10μm, dried at 90°C, and rolled to obtain a single-sided coated 1# positive electrode plate. The 1# positive electrode plate has a compactness of 2.3g / cc and an active material loading of 22mg / cm 2 .
[0146] The 1# lithium ion battery is a half-cell. The preparation method of the 1# lithium ion battery is as follows: placing a 1# positive electrode plate, a separator (Celgard2400), and a lithium plate in a button battery in order, injecting an electrolyte (a mixed solution of ethylene carbonate (EC) and diethyl carbonate (EMC) (v / v=1:1) containing 1 mol / L LiPF6, and fluoroethylene carbonate (FEC), with the addition amount of FEC being 10wt%), encapsulating the button battery, and standing for 12 hours to obtain a 1# lithium ion battery.
[0147] Example 2-Example 8
[0148] Embodiments 2 to 6 of the present invention respectively provide corresponding lithium-based positive electrode materials, positive electrode sheets prepared based on the corresponding lithium-based positive electrode materials, and lithium-ion batteries obtained based on the corresponding positive electrode sheets, wherein all of these lithium-ion batteries are in the form of half-cells. Embodiments 7 to 8 of the present invention respectively provide corresponding sodium-based positive electrode materials, positive electrode sheets prepared based on the corresponding sodium-based positive electrode materials, and sodium-ion batteries obtained based on the corresponding positive electrode sheets, wherein all of these sodium-ion batteries are in the form of half-cells.
[0149] Examples 2 to 6 are basically the same as Example 1 in terms of the preparation methods of lithium-based positive electrode materials, positive electrode sheets, and lithium-ion batteries, and the only difference is that the types of positive electrode active materials and active ion supplement materials are different and the ratios of the two are different. Also, Examples 7 to 8 are basically the same as Example 1 in terms of the preparation methods of lithium-based positive electrode materials, positive electrode sheets, and lithium-ion batteries, and the only difference is that: (1) the types of positive electrode active materials and active ion supplement materials are different and the ratios of the two are different. (2) Sodium sheets are used.
[0150] See Table 1 for the differences mentioned above.
[0151] Table 1
[0152]
[0153] Among them, NMC811 mentioned in Table 1 is LiNi 0.8 Mn 0.1 Co 0.1 O2, which is a nickel-rich layered oxide.
[0154] Comparative Example 1
[0155] Comparative Example 1 provides a corresponding lithium-based positive electrode material, a positive electrode sheet prepared based on the corresponding lithium-based positive electrode material, and a lithium-ion battery obtained based on the corresponding positive electrode sheet.
[0156] The difference between Comparative Example 1 and Example 1 is that no lithium supplement material is added to the positive electrode plate, and the rest is the same as Example 1.
[0157] Comparative Example 2-Comparative Example 6
[0158] Compared with Example 1, Comparative Example 2 differs in that the positive electrode active material and the active ion supplement material in the positive electrode plate are mixed in a conventional manner, and the rest is the same as Example 1.
[0159] The preparation method of the positive electrode sheet in the comparative example is as follows:
[0160] 45.6g LiFePO4, 2.4g Li6CoO4, 0.5g carbon nanotubes and 1.5g polyvinylidene fluoride were mechanically mixed, and then N-methylpyrrolidone was added as a solvent to prepare a slurry with a solid content of 65wt%, and stirred evenly to obtain a uniform positive electrode slurry. The positive electrode slurry was coated on an aluminum foil current collector with a thickness of 10μm, dried at 90℃, and rolled to obtain a single-sided coated positive electrode sheet. The compression density of the positive electrode sheet was 2.3g / cc and the active material loading was 22mg / cm 2 .
[0161] Compared with Example 3, Comparative Example 3 differs in that the positive electrode active material and the lithium supplement material in the positive electrode plate are mixed in a conventional manner, and the rest are the same as Example 1. On this basis, the preparation method of the positive electrode plate can refer to Comparative Example 2.
[0162] The difference between Comparative Example 4 and Example 5 is that the positive electrode active material and the lithium supplement material in the positive electrode plate are mixed in a conventional manner, and the rest are the same as Example 1. On this basis, the preparation method of the positive electrode plate can refer to Comparative Example 2.
[0163] The difference between Comparative Example 5 and Example 7 is that the positive electrode active material and the lithium supplement material in the positive electrode plate are mixed in a conventional manner, and the rest are the same as Example 1. On this basis, the preparation method of the positive electrode plate can refer to Comparative Example 2.
[0164] The difference between Comparative Example 6 and Example 8 is that the positive electrode active material and the lithium supplement material in the positive electrode plate are mixed in a conventional manner, and the rest are the same as Example 1. On this basis, the preparation method of the positive electrode plate can refer to Comparative Example 2.
[0165] For the above mentioned differences, please refer to Table 2.
[0166] Table 2
[0167]
[0168] Test Example 1
[0169] This test example 1 tests the element distribution, structural morphology, and distribution of the positive electrode active material and active ion supplement material in the positive electrode material provided in Example 2. For element distribution, see Table 3, which is shown below.
[0170] Table 3
[0171] element Weight Percent Atomic Percent C 35.97 57.28 O 23.06 27.56 P 4.49 2.77 Fe 30.54 10.46 Co 5.94 1.93 Total 100% 100%
[0172] The surface morphology of the positive electrode material of Example 2 is shown in Figure 3 The cross-sectional morphology of the positive electrode material of Example 2 is shown in Figure 4 The EDS (Energy Dispersive Spectroscopy) spectrum of the positive electrode material of Example 2 is shown in Figure 5 The distribution state of the cobalt (Co) element in the positive electrode material of Example 2 is shown in Figure 6 The distribution state of the cobalt (Co) element represents the distribution state of the active ion supplement material, where the cobalt (Co) element is Figure 6 The distribution state of the iron (Fe) element in the positive electrode material of Example 2 is shown in Figure 7The distribution state of the iron (Fe) element represents the distribution state of the positive electrode active material, where the iron (Fe) element is Figure 7 Indicated by grayish-white particles or areas.
[0173] pass Figure 3-Figure 7 It can be seen that for the positive electrode material provided in Example 2, the active ion supplement material particles are in close contact with the positive electrode active material particles, and the active ion supplement material particles are uniformly dispersed in the gaps of the positive electrode active material accumulation body, which indicates that the active ion supplement particles are successfully embedded in the interior of the positive electrode active material agglomerates, and the active ion supplement material and the positive electrode active material are both in a highly uniform dispersion state.
[0174] Test Example 2
[0175] This test example 2 tests the performance of the positive electrode materials, positive electrode sheets and lithium ion / sodium ion batteries provided in Examples 1 to 8 and Comparative Examples 1 to 6. The specific test items are as follows:
[0176] (1) Slurry stability: After the positive electrode slurry is prepared, a portion of the positive electrode slurry is taken and left to stand for 2 hours, and its state is observed and recorded.
[0177] (2) First coulombic efficiency: The first discharge capacity and first charge capacity of each of the above lithium-ion / sodium-ion batteries were measured using a blue battery tester CT3001A, and the first coulombic efficiency was calculated, where first coulombic efficiency = first discharge capacity / first charge capacity × 100%.
[0178] (3) Based on the theoretical capacity of the positive electrode active material and its proportion, the capacity of the active ion supplement material can be inferred, that is, the capacity of the active ion supplement material.
[0179] (4) Cycle retention rate: The capacity retention rate of the above-mentioned lithium-ion / sodium-ion battery after 100 cycles at a charge and discharge rate of 0.2C / 0.2C.
[0180] The test results of the above items are shown in Table 4.
[0181] Table 4
[0182]
[0183] As can be seen from Table 4, for high-capacity lithium-supplementing materials / sodium-supplementing materials (Examples 1-4, 6 and 8, and Comparative Examples 2-3 and 6), if the conventional mixing method is used to mix with the positive electrode active material (Comparative Examples 2-3 and 6), the positive electrode slurry will show different degrees of sedimentation after standing, and the stability is poor. It is speculated that the high residual alkali on the surface of the lithium-supplementing / sodium-supplementing material causes the polyvinylidene fluoride to fail and the positive electrode slurry is jelly-like. However, for the composite positive electrode slurry (Examples 1-4, 6 and 8) using the "embedded" lithium-supplementing / sodium-supplementing" embodiments of the present disclosure, the positive electrode slurry remains stable after standing without sedimentation, indicating that the structure of the positive electrode material enables the protection of high-capacity lithium-supplementing materials / sodium-supplementing materials and improves process compatibility.
[0184] For batteries obtained by conventionally mixing positive electrode active materials with active ion supplementary materials, it is estimated based on the discharge capacity. The capacity of the lithium supplementary material / sodium supplementary material is relatively low (only 10%-40% of the theoretical capacity), which means that during the preparation process, the lithium supplementary material / sodium supplementary material is affected by air, humidity, etc., and partially fails, and fails to exert the theoretical capacity. The capacity retention rate of the corresponding battery after 100 cycles is low (60%-75%), indicating that the failed lithium supplementary material / sodium supplementary material has side effects on the positive electrode as a whole, which is presumably due to increased polarization, gas production, catalytic side reactions of the battery cell, etc.
[0185] The positive electrode material provided in the embodiment of the present disclosure has an active ion supplement material capacity of 400mAh / g-750mAh / g, which is close to its theoretical capacity, and has good battery cycle stability (>90%@100cls), proving that the structure of the positive electrode material increases the stability of the lithium supplement material / sodium supplement material without causing additional side reactions to the battery system.
[0186] For organic lithium-replenishing materials / sodium-replenishing materials (Comparative Examples 4 and 5, and Examples 5 and 7), the lithium-replenishing / sodium-replenishing capacity of Comparative Examples 4 and 5 cannot be fully utilized, presumably because the decomposition potential of the organic lithium-replenishing materials / sodium-replenishing materials is high, and the contact is poor in the ordinary mixing method, and they cannot be decomposed within the voltage window. However, the lithium-replenishing / sodium-replenishing capacity of Examples 5 and 7 is close to the theoretical value, indicating that the "embedded" composite structure of the positive electrode material has better contact with the lithium-replenishing material / sodium-replenishing material, greatly reducing its decomposition overpotential, decomposing within the designed voltage window, and the corresponding battery cycle stability is also more excellent (>93%@100cls).
[0187] The above description is only for the purpose of facilitating those skilled in the art to understand the technical solution of the present disclosure and is not intended to limit the present disclosure. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present disclosure shall be included in the protection scope of the present disclosure.
Claims
1. A positive electrode material, characterized in that: The positive electrode material comprises positive electrode active material aggregates and active ion supplementary materials, wherein the positive electrode active material aggregates are formed by stacking the positive electrode active materials; The active ion supplement material is located at least in a plurality of gaps of the positive electrode active material agglomerates, and the active ion supplement material is bonded to the positive electrode active material.
2. The positive electrode material according to claim 1, characterized in that The average particle size of the positive electrode material is 2um-20um, and the average particle size of the active ion supplement material is 10nm-2000nm.
3. The positive electrode material according to claim 1, characterized in that Based on 100 parts by weight of the positive electrode material, the weight of the active ion supplement material is 1 part to 10 parts.
4. The positive electrode material according to claim 1, characterized in that The density of the positive electrode material is greater than 90%.
5. The positive electrode material according to any one of claims 1 to 4, characterized in that Carbon simple substance and / or carbon compound exist between different particles of the positive electrode active material and between the positive electrode active material and the active ion supplement material, and the carbon simple substance and / or carbon compound are used to provide chemical bonding force.
6. The positive electrode material according to claim 1, characterized in that The mass ratio of the active ion supplement material located in the plurality of gaps of the positive electrode active material agglomerates to the total mass of the active ion supplement material is greater than or equal to 90%.
7. The positive electrode material according to any one of claims 1 to 6, characterized in that The positive electrode active material agglomerates are formed by stacking lithium-based positive electrode active materials, and the active ion supplement material is a lithium supplement material.
8. The positive electrode material according to any one of claims 1 to 6, characterized in that The positive electrode active material agglomerates are formed by stacking sodium-based positive electrode active materials, and the active ion supplement material is a sodium supplement material.
9. The positive electrode material according to claim 7, characterized in that The lithium-based positive electrode active material is selected from at least one of lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, and lithium-rich layered oxide; The lithium supplement material is selected from at least one of Li3N, LiF, Li2O2, Li2O, Li x M y O z where 0 < x ≤ 6, 0 < y ≤ 4, 0 ≤ z ≤ 5, and M is selected from at least one of C, S, Si, Fe, Al, Co, Mn, Zn, Ni, Sb, Te, Ti.
10. The positive electrode material according to claim 8, characterized in that The sodium-based positive electrode active material is selected from at least one of sodium vanadium phosphate, sodium vanadium fluorophosphate, sodium manganese phosphate, sodium iron phosphate, sodium cobaltate, sodium manganate, sodium nickelate, sodium vanadate, and sodium nickel iron manganate; The sodium supplement material is selected from at least one of Na3N, NaF, Na2O2, Na2O, Na x M y O z where 0 < x ≤ 6, 0 < y ≤ 4, 0 ≤ z ≤ 5, and M is selected from at least one of C, S, Si, Fe, Al, Co, Mn, Zn, Ni, Sb, Te, Ti.
11. The positive electrode material according to any one of claims 1 to 10, characterized in that: The positive electrode material further comprises a coating layer, which is coated on the outside of the positive electrode active material agglomerate and is used to enhance the structural stability of the positive electrode material.
12. A positive electrode sheet, characterized in that: The positive electrode sheet comprises the positive electrode material according to any one of claims 1 to 11.
13. An electrochemical energy storage battery, characterized in that: The electrochemical energy storage battery includes a positive electrode plate, and the positive electrode plate is as described in claim 12.
14. The electrochemical energy storage cell according to claim 13, characterized in that: The electrochemical energy storage battery includes a lithium ion battery and a sodium ion battery.
15. A method for preparing a positive electrode material, characterized in that: The positive electrode material is as described in any one of claims 1 to 11; The preparation method of the positive electrode material comprises: The positive electrode active material, the active ion supplement material, the organic binder and the solvent are uniformly mixed to form a raw material solution; Under an inert atmosphere, spray drying the raw material liquid to obtain a granular intermediate; The granular intermediate is calcined under an inert atmosphere to obtain the positive electrode material.
16. The method for preparing the positive electrode material according to claim 15, characterized in that: The solid content of the raw material liquid is 10%-50%, and the viscosity is 1000cP-5000cP.
17. The method for preparing the positive electrode material according to claim 15, characterized in that: The spray drying operation parameters meet at least one of the following parameters: air inlet temperature is 150°C-200°C, air outlet temperature is 90°C-120°C, peristaltic pump speed is 100ml / h-1000ml / h, and nozzle diameter is 0.5mm-2mm.
18. The method for preparing the positive electrode material according to claim 15, characterized in that: The operating parameters of the calcination process meet at least one of the following parameters: the calcination temperature is 400° C.-700° C., and the calcination time is 6 hours-12 hours.
Citation Information
Cited By
Positive electrode material and preparation method thereof, positive plate and secondary battery
CN120933346A
Positive electrode sheet for sodium ion battery, battery, battery pack, and electric device
WO2026158103A1
